STUDYING GENDER THROUGH CASTE LENSES IN SHARANKUMAR LIMBALE’S THE DALIT BRAHMINS AND OTHER STORIES - Narsing, Balande Chandoba (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Dalit literature in India has been playing a very important role in acquainting readers with Dalits’ world of suffering, oppression, and resistance. This research paper explores the complex interplay of gender and caste in the selected short stories from Sharankumar Limbale’s short story collection, The Dalit Brahmins and Other Stories (2018). The paper focuses on short stories, “Ratna”, “Madhavi”, “Soni” and “Niloo”. Through a comparative analysis of these narratives, the paper highlights how the characters’ experiences are shaped by their caste identities and societal roles. Ratna and Soni, representing lower-caste Dalit women, have to live a life of oppression, violence, and societal neglect, while Madhavi and Niloo, as upper-caste women, embody privilege yet remain complicit in perpetuating caste hierarchies. The stories illustrate the clear contrasts in their lived realities, revealing how caste influences their bodies, autonomy, and relationships. The paper critically examines the ‘lived experiences’ of these women, whose bodies become contested terrains in a socio-cultural landscape rife with systemic inequalities. The paper explores the symbolism of the female body as a site of cultural meaning, where upper-caste women are often idealised and protected, while Dalit women face objectification and exploitation. By examining Limbale’s heart-rending storytelling, the paper contributes to the discourse on gender equality and social justice, highlighting the urgent need to address the systemic oppression faced by women in a casteist society. Through this analysis, the paper aims to illuminate the broader implications of caste-based discrimination and its impact on gender dynamics in contemporary India.